A case of bradycardia during SARS CoV-2 infection in a 14-year-old child. Issue 7 (3rd July 2021) - Kilicaslan, Onder; Isancli, Didem Kizmaz; Ulutas, Omer Yilmaz; Ergin, Selma Oktay; Karbuz, Adem
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) has caused an infectious disease that affects multiple organs. Recently, the cardiological effects of the virus have also been striking. To the best of our knowledge, there are no SARS CoV-2 positive paediatric cases reported with sinus bradycardia in the literature. Case presentation: A 14-year-old male patient presented with complaints of abdominal pain and fatigue. The heart rate of the patient, whose grandmother was found to be positive for SARS CoV-2 test, ranged between 43 and 60/min, the heart sounds were normal. There was no known history of cardiological disorder in the patient and his family. His laboratory findings were; normal Troponin I, elevated C Reactive protein, normal Haemoglobin, normal CK-MB, mildly elevated D-Dimer. Electrocardiography of the patient was evaluated as sinus bradycardia. There was no pathological finding in his echocardiography. The SARS CoV-2 PCR test was positive. In his follow-up, the heart rate decreased to 50 beats per minute while awake and 43 beats per minute while sleeping. The patient had a bradycardic course until the 4th day of hospitalisation. Control SARS CoV-2 PCR test was negative. He was discharged on the 8th day. Conclusion: It's understood that SARS-CoV-2 is responsible for multiple cardiac manifestations. The most common bradyarrhythmia associated with SARS CoV-2 reported worldwide is sinus bradycardia and complete heart block. In order to contribute to the literature, we present a 14-year-old paediatric patient with positive SARS CoV-2 PCR test who has normal cardiac tests and sinus bradycardia.